Protective immunity differs between routes of administration of attenuated malaria parasites independent of parasite liver load - Haeberlein, Simone; Chevalley-Maurel, Séverine; Ozir-Fazalalikhan, Arifa; Koppejan, Hester; Winkel, Beatrice M. F.; Ramesar, Jai; Khan, Shahid M.; Sauerwein, Robert W.; Roestenberg, Meta; Janse, Chris J.; Smits, Hermelijn H.; Franke-Fayard, Blandine (Scientific reports, 2017)
In humans and murine models of malaria, intradermal immunization (ID-I) with genetically attenuated sporozoites that arrest in liver induces lower protective immunity than intravenous immunization (IV-I). It is unclear whether this difference is caused by fewer sporozoites migrating into the liver or by suboptimal hepatic and injection site-dependent immune responses. We therefore developed a Plasmodium yoelii immunization/boost/challenge model to examine parasite liver loads as well as hepatic and lymph node immune responses in protected and unprotected ID-I and IV-I animals. Despite introducing the same numbers of genetically attenuated parasites in the liver, ID-I resulted in lower sterile protection (53–68%) than IV-I (93–95%). Unprotected mice developed less sporozoite-specific CD8 + and CD4 + effector T-cell responses than protected mice. After immunization, ID-I mice showed more interleukin-10-producing B and T cells in livers and skin-draining lymph nodes, but fewer hepatic CD8 memory T cells and CD8 + dendritic cells compared to IV-I mice. Our results indicate that the lower protection efficacy obtained by intradermal sporozoite administration is not linked to low hepatic parasite numbers as presumed before, but correlates with a shift towards regulatory immune responses. Overcoming these immune suppressive responses is important not only for live-attenuated malaria vaccines but also for other live vaccines administered in the skin.